2014
DOI: 10.1371/journal.pone.0105061
|View full text |Cite
|
Sign up to set email alerts
|

Expression Analysis of a Stress-Related Phosphoinositide-Specific Phospholipase C Gene in Wheat (Triticum aestivum L.)

Abstract: Plant phosphoinositide-specific phospholipases C (PI-PLCs) function in several essential plant processes associated with either development or environmental stress. In this report, we examined the expression patterns of TaPLC1 under drought and high salinity stress at the transcriptional and post-transcriptional levels. TaPLC1 mRNA was expressed in all wheat organs examined. U73122 and edelfosine, the PLC inhibitor, impaired seedling growth and enhanced seedling sensitivity to drought and high salinity stress.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…The PLC/DGK pathway is one of the most important signaling networks in response to biotic and abiotic stresses [1,5,18]. Our previous work revealed the function of TaPLC1 in controlling seedling growth and adapting to drought and salt stress [22], while the present study is focused on the role of DGK genes in wheat.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The PLC/DGK pathway is one of the most important signaling networks in response to biotic and abiotic stresses [1,5,18]. Our previous work revealed the function of TaPLC1 in controlling seedling growth and adapting to drought and salt stress [22], while the present study is focused on the role of DGK genes in wheat.…”
Section: Discussionmentioning
confidence: 90%
“…Additionally, overexpression of the wheat phospholipase D gene TaPLDα has been shown to enhance tolerance to drought and osmotic stress in transgenic Arabidopsis thaliana [3]. Previously, we had measured the TaPLC expression patterns at both the transcriptional and protein levels in response to drought and salinity stress, and our research indicated the possible roles of TaPLC1 in mediating seedling growth and responding to drought and salinity stress [22]. However, the molecular functions of lipid messengers remain unclear in wheat.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The production of lipids and lipid derivatives is controlled by different families of enzymes, including phospholipases, lipid kinases and phosphatases (Wang 2004;). PI-PLC activity and its enzymatic products (IP 3 and DAG) are involved in regulating the plant salt stress response; Tripathy et al 2012;Zhang et al 2014;Zhang et al 2015). Among these PI-PLC genes, the roles of NtPLCδ1 in salt and osmotic stresses responses (Tripathy et al 2012), AtPLC1 in ABA signal secondary responses (Sanchez & Chua 2001, and AtPLC5 in leaf senescence (Zhang et al 2015) have been confirmed.…”
Section: Discussionmentioning
confidence: 93%
“…PI‐PLC activity and its enzymatic products (IP 3 and DAG) are involved in regulating the plant salt stress response; however, which member(s) of the PI‐PLC family is responsible and how it regulates the salt stress response remain largely unknown. The transcription of multiple PI‐PLC genes, such as AtPLC1 , 3 , 4‐7 in Arabidopsis, NtPLCδ1 in tobacco ( N. tobacco ), VrPLC3 in mung bean (Vigna radiate) , PtoPLC1 in poplar ( Populus tomentosa ) and TaPLC1 in wheat ( Triticum aestivum ), is significantly induced by salt and other abiotic or biotic stresses (Hirayama et al ; Kim et al ; Tasma et al ; Tripathy et al ; Zhang et al ; Zhang et al ). Among these PI‐PLC genes, the roles of NtPLCδ1 in salt and osmotic stresses responses (Tripathy et al ), AtPLC1 in ABA signal secondary responses (Sanchez & Chua , and AtPLC5 in leaf senescence (Zhang et al ) have been confirmed.…”
Section: Discussionmentioning
confidence: 99%